EMPOWERING EFL LEARNERS: ANALYSIS OF STUDENT’S BOOK FOR LEARNER AUTONOMY IMPLEMENTATION - Astri Winandari Berlin; Yanty Wirza; Madaresita Madaresita; Ayu Lestari; Faksi Rana Al-Kahfi (TELL - US JOURNAL, 2025)
Learner autonomy has gained attention in English for Foreign Language (EFL) study context, but research on its promotion through EFL textbooks used in Indonesian Classroom remains limited. This study addresses this gap by evaluating ‘English in Mind’ student’s textbook facilitation of learner autonomy. A qualitative case study was employed, using Levels of Learner Autonomy Implementation Framework to analyze the textbook. The result show that the textbook facilitates learner autonomy to varying degrees, with Awareness level being the most prominent. The facilitation of higher levels of autonomy, namely Involvement, Intervention, Creation, and Transcendence were less frequent. They suggest that while the textbook supports foundational autonomy, there are gaps in promoting higher-level autonomy. This study contributes to educational theory by illustrating how textbooks can support learner autonomy in a context with limited studies. Practically, it offers insights into how textbooks can be used to foster learner autonomy in EFL classrooms. From a policy perspective, while the findings suggest that the textbook lays a foundation for learner autonomy promotion, targeted policy initiatives are needed to systematically integrate higher-level autonomy tasks and support their effective implementation in Indonesian EFL classrooms.